Leadership of place in virtual environments. (February 2022) - Schmidt, Gordon B; Van Dellen, Stephanie A
Place and space concepts help to illuminate how the place an organization inhabits and related beliefs have a significant impact on leadership processes. While places often have a physical presence, a sense of place is socially constructed by those who interact in it. This article offers analysis of how virtual environments can be seen as socially constructed places and how that conceptualization impacts leadership, both in the environment acting as a leadership substitute and how people engage in virtual leadership. This conceptual analysis occurs by integrating existing literature on space, place, technology affordances, and virtual leadership, as well as analyzing current virtual work environments and virtual leaders. We illustrate how virtual places can offer affordances for leadership sensemaking of political leaders, virtual place-making by social media influencers, algorithmic leadership, and shared leadership in the gig economy. We close the article by discussing how current leaders can consider the affordances of virtual environments and needed future needed research.